2008
DOI: 10.1590/s0102-05362008000100022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion-cooking in total carotenoids content in cream and orange flesh sweet potato cultivars

Abstract: Sweet potato (Ipomoea batatas) is a food crop that supplies energy, minerals and vitamins C and B. Some cultivars are very rich in carotenoids (pro-vitamin A). In this study were evaluated and compared the total carotenoids content of two cultivars and the losses on the dehydrated extruded sweet potato flour. Samples from organic and conventional crops were analyzed, in the form of fresh and dehydrated extruded samples. Total carotenoids content of the fresh product, expressed on wet basis, was of 437 µg 100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…An Acad Bras Cienc (2018) 90 (1) 288 AMANDA C. NOGUEIRA et al Fonseca et al (2008), who found 101 and 4.38 μg/g β-carotene in orange and cream-colored sweet potatoes, respectively, and 293.97 µg/g and 15.87 μg/g total carotenoids in the respective flours.…”
Section: Characterization Of the Raw Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…An Acad Bras Cienc (2018) 90 (1) 288 AMANDA C. NOGUEIRA et al Fonseca et al (2008), who found 101 and 4.38 μg/g β-carotene in orange and cream-colored sweet potatoes, respectively, and 293.97 µg/g and 15.87 μg/g total carotenoids in the respective flours.…”
Section: Characterization Of the Raw Materialsmentioning
confidence: 99%
“…During processing, carotenoids in food are unstable to the action of heat, light, and oxygen, and may suffer total or partial isomerization and degrade depending on time and temperature conditions (Fonseca et al 2008). Therefore, these conditions should be taken into account when processing yellow sweet potatoes, once their high perishability during storage can be prevented by dehydration processes to extend shelf life (Rodriguez-Amaya et al 2011, Alves et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the nutritional quality of processed alfalfa does vary and many studies have shown that the application of thermal treatments to produce alfalfa meal decreases the content of carotenoids (Boileau and Erdman, 2004;Fonseca et al, 2008). In addition, Zilic et al (2010), Nurnberg et al (2006 and Alfaiea et al (2010) observed that some fatty acids (FA), mainly long chain FA, tend to be modified or become oxidized during the thermal treatment of soybeans, pork or beef, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Beta-carotene content in light yellow and purple fleshed ones were in the range of 0.1-0.6 mg/100 g, fresh weight (FW) in a study reported by Lund and Smooth in [43]. Fonseca et al [44] examined the orange-fleshed sweetpotato root (IAPAR 69) manufactured through the organic system production system and discovered 10,120 µg per 100g (d.b. ), calculated in β-carotene equivalent.…”
Section: Vitamin a And Carotenoidsmentioning
confidence: 98%